2015
DOI: 10.14745/ccdr.v41i03a02
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring invasive bacterial diseases in the North American Arctic via the International Circumpolar Surveillance Project

Abstract: This paper summarizes the most recent Invasive Bacterial Diseases (IBD) Working Group meeting of the International Circumpolar Surveillance (ICS) project. The ICS is a population-based surveillance network for invasive bacterial diseases that provides a mechanism to determine changes in incidence rates and antimicrobial resistance. The meeting took place in Montreal, Canada on February 12-13, 2014. Data were included from participating Canadian provincial and territorial jurisdictions as well as from the State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…At the time, laboratory surveillance activities at the National Microbiology Laboratory (NML) had identified a significant percentage of serotype a isolates that were responsible for invasive H. influenzae disease (20). Consultation with the Council of Provincial and Territorial Medical Officers of Health and the subsequent review of invasive Hia data from the northern Canadian territories collected via the International Circumpolar Surveillance System confirmed that Hia was a significant emerging pathogen (21,22) causing severe invasive disease for which no vaccine was currently available. Building on the success of the Hib conjugate vaccine developed in the 1980s for control of invasive Hib disease, the similarities of the biology of Hia and Hib, and the diseases they cause, research was initiated to lay the foundation for developing a Hia conjugate vaccine.…”
Section: Inter-departmental Collaborationmentioning
confidence: 99%
“…At the time, laboratory surveillance activities at the National Microbiology Laboratory (NML) had identified a significant percentage of serotype a isolates that were responsible for invasive H. influenzae disease (20). Consultation with the Council of Provincial and Territorial Medical Officers of Health and the subsequent review of invasive Hia data from the northern Canadian territories collected via the International Circumpolar Surveillance System confirmed that Hia was a significant emerging pathogen (21,22) causing severe invasive disease for which no vaccine was currently available. Building on the success of the Hib conjugate vaccine developed in the 1980s for control of invasive Hib disease, the similarities of the biology of Hia and Hib, and the diseases they cause, research was initiated to lay the foundation for developing a Hia conjugate vaccine.…”
Section: Inter-departmental Collaborationmentioning
confidence: 99%